Inside the wilderness of mirrors Australia and the threat from the Soviet Union in the Cold War and Russia today - Dibb, Paul 1939- (Melbourne University Press, 2018)
Throughout the Cold War Paul Dibb worked with the highest levels of Australian and American intelligence, and was one of very few Australian officials to be given the top-secret security clearance for access to Pine Gap. Only the most senior intelligence officers in both the US and Australia held this clearance - and even then on a strict 'need to know' basis. Inside the Wilderness of Mirrors is Paul's unique insight into how Australia saw the threat from the Soviet Union during the Cold War era and beyond. This insider's account of Australian defence strategy reveals the crucial importance of the US-Australian base at Pine Gap and why Moscow targeted it for nuclear attack, and how it felt to be an expert on the Soviet Union at a time when those who dared to study the Soviet Union were necessarily subject to suspicion from their Australian colleagues. Inside the Wilderness of Mirrors concludes by examining the ways in which contemporary Russia presents a continuing threat to the international order
Keywords: Geschichte 1945-; Internationale Politik; Ost-West-Konflikt; Australien; Russland; Australian history; Australian; Australia / Foreign relations / Soviet Union; Australia / Foreign relations / Russia (Federation); Soviet Union / Foreign relations / Australia; Russia (Federation) / Foreign relations / Australia; Cold War